2008
DOI: 10.1002/hbm.20502
|View full text |Cite
|
Sign up to set email alerts
|

Cortical dysfunction in patients with Huntington's disease during working memory performance

Abstract: Previous functional neuroimaging studies on executive function suggested multiple functionally aberrant cortical regions in patients with Huntington's disease (HD). However, little is known about the neural mechanisms of working memory (WM) function in this patient population. The objective of this study was to investigate the functional neuroanatomy of WM in HD patients. We used event-related functional magnetic resonance imaging and a parametric verbal WM task to investigate cerebral function during WM perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 63 publications
6
43
2
2
Order By: Relevance
“…Functional MRI studies probing cognitive and motor processes in symp-HD individuals provide a largely inconclusive picture of functional reorganization in the cerebral cortex, with decreased activity in occipital and parietal cortices 55 as well as both increased 55,56 and decreased activation in the bilateral middle frontal gyrus. 57 In such task-based studies, however, heterogeneity in neuronal responses is variable, likely reflecting stage of disease, cognitive status and/or differences in behavioural performance. Resting state BOLD, on the other hand, provides a task-independent measure of neuronal activity and synchronization and, hence, may better reflect functional reorganization of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional MRI studies probing cognitive and motor processes in symp-HD individuals provide a largely inconclusive picture of functional reorganization in the cerebral cortex, with decreased activity in occipital and parietal cortices 55 as well as both increased 55,56 and decreased activation in the bilateral middle frontal gyrus. 57 In such task-based studies, however, heterogeneity in neuronal responses is variable, likely reflecting stage of disease, cognitive status and/or differences in behavioural performance. Resting state BOLD, on the other hand, provides a task-independent measure of neuronal activity and synchronization and, hence, may better reflect functional reorganization of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The executive control network also showed impaired synchronization with the putamen and superior parietal area. Postmortem and imaging studies have shown significant neurodegeneration of the posterior putamen in patients with Huntington disease, [57][58][59] with the ventral anterior portion rela tively spared. 60 Our findings suggest that this focal neuro degeneration may result in a functional disconnection of the corticostriatal cognitive loop from the frontal executive system of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…For example, executive dysfunction on cognitive tasks (i.e., set shifting, response inhibition) has been linked with the dorsolateralsubcortical circuit (4) and dorsolateral prefrontal cortex deficits (5). Motor deficits in HD have also been related with abnormalities of the fronto-subcortical circuits (5,6). Unfortunately, the behavioral manifestations of this suspected "frontal"-subcortical dysfunction have been less widely examined in patients with HD.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complex phenotypic heterogeneity of HD, another research challenge is to find highly sensitive screening methods (Esmaeilzadeh et al, 2011). Magnetic Resonance Imaging (MRI) has recently contributed to an improved understanding of striatal atrophy and cortical dysfunction (Paulsen et al, 2004;Rosas et al, 2004;Wolf et al, 2007Wolf et al, , 2009). Moreover, diffusion-based MRI techniques are the only non-invasive imaging techniques that can be applied to study the pathways and connections of not only the human brain, but also of the rodent brain (Douaud et al, 2009;Mascalchi et al, 2004;Reading et al, 2005;Rosas et al, 2006;Seppi et al, 2006;Van Camp et al, 2012).…”
Section: Introductionmentioning
confidence: 99%